Tuberculosis and its impact worldwide and in Colombia, a literature review. - Hernández-Rico, Álvaro Antonio (2022)
Aim: Tuberculosis is caused by the Mycobacterium tuberculosis complex, being the thirteenth cause of death worldwide, and one of the oldest known diseases that affect world population. This pathology frequently occurs in comunities living in overcrowded situations and those with a low socioeconomic status; In addition, it frequently occurs in patients with HIV and other immunosuppressions. This disease is too important for global public health, so, the World Health Organization, in the objectives for sustainable development, states in its objective 3 "Ensure a healthy life and promote well-being for all at all ages", within of which include “By 2030, end the epidemics of AIDS, tuberculosis, malaria and neglected tropical diseases and combat hepatitis, waterborne diseases and other communicable diseases”. This review article has discussed the history, epidemiology, risk factors, the regulatory framework and the costs derived from the disease, both worldwide and in Colombia. The data show the current state of the disease, both for drug-sensitive tuberculosis and multidrug-resistant tuberculosis, were analyzed and detailed. This review article has been written after an extensive review of the available international and national literature, in order to better understand the disease, and work towards eliminating tuberculosis from the earth in the near future.